Sasaran Dakwah Non-Muslim di Malaysia: Suatu Kajian Tentang Keadaan Orang Asli di Perkampungan Orang Asli Ulu Kuang, Gombak, Selangor - Mohd. Zin, Ab. Aziz (Jurnal Usuluddin, 1995)
Malaysia has a number various aborigines community which have their own civilization. Furthermore, the Islamic way of life is not well known among this community since they are remote from other Muslim community. Due to this circumstances, it is an important to make sure that they received the teaching of Islam and practice it as the way of life. Therefore, this article describes the background of the aborigines community at Ulu Kuang to ensure the effectiveness of Islam among this community.